Designing of Guidance Paths for Quality Assurance of Technology Academic Programs - Hussein Mohammed Ahmed (University of Science and Technology, Yemen, 2014)
Abstract:Technical education is considered  one of  the important educational courses in the today world, Because of  its direct contribution in transfer and development of technology in all aspects of  life. And the impotence  of  this type of education comes from its direct associations to meet the rapid changes of  the market needs. However, the most prominent challenges facing this type of education is the quality of  its academic technical programs and how to improve it to suits the market needs . Also the research included a proposal to build six guiding paths which they complete each other, and had branched from them a number of  axis to form a structure to ensure the quality of education in technical colleges, where those paths are the main source for the construction of academic standards, they define the duties of the college faculty, academic department and associated committees with them, and the rest of  departments and  units of  college. And the requirements of  these duties in the way that ensures the quality.The main paths are :1.     Educational events.2.     Requirements of quality assurance.3.     Requirements of quality documentation.4.     Responsibility of  the college faculty.5.     Benchmarking track.6.     Stages of quality application.   Keywords: Quality assurance, Extension , paths, educational process, benchmarking.